1930
DOI: 10.1007/bf01484764
|View full text |Cite
|
Sign up to set email alerts
|

Lösungsmittelwirkung bei Kautschuk

Abstract: J)7 ~epm/ze L/z~re 3u6~nz3' Fig. 1 (3renzflfiche von Luft und Olas Totalreflexion erffihrt.Wie sehr wir auch die Membrane zwischen den beiden Gl~isern komprimieren, so ist es doch praktisch unmOglich, eine letzte diinnste Luftschicht auszuschalten, welche infolge Adsorption am Qlase haften bleibt und gen~igt, um die Totalreflexion der sehdigen Beleuchtungsstrahlen zu bewirken. Da also tier Beleuchtungsstrahl reflektiert wird, noch eheer in die Objektmasse eindringen konnte, ist kS ohne weiteres verst~indlich, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1932
1932
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Figure 5 illustrates the interaction (12,16,21,49,50,51,69) when such an adsorbent, fine carbon black, is added with convenient stirring to a dilute solution of Halo C GR-S containing 19% microgel. A similar fractional adsorption curve is shown in Figure 6 for GR-S modified so that it contained no microgel.…”
Section: Microgel and Molecular Weight Distributionmentioning
confidence: 99%
“…Figure 5 illustrates the interaction (12,16,21,49,50,51,69) when such an adsorbent, fine carbon black, is added with convenient stirring to a dilute solution of Halo C GR-S containing 19% microgel. A similar fractional adsorption curve is shown in Figure 6 for GR-S modified so that it contained no microgel.…”
Section: Microgel and Molecular Weight Distributionmentioning
confidence: 99%
“…Theory. It has been reported that a mixture of rubber and carbon black is not completely dispersed by a solvent, but that the stock is swollen by the solvent and part of the rubber is extracted, leaving all of the carbon black in the swollen gel (4,10,24).…”
Section: Bound Rubbermentioning
confidence: 99%